Translating Research Into Practice: Is Evidence-Based Medicine Being Practiced in Military-Relevant Orthopedic Trauma?. (1st April 2015) - Niles, Sarah E.; Balazs, George C.; Cawley, Christina; Bosse, Michael; Mackenzie, Ellen; Li, Yaunzhang; Andersen, Romney C.
ABSTRACT: Orthopedic trauma remains one of the most survivable battlefield injuries seen in modern conflicts. Translating research into practice is a critical bridge that permits surgeons to further optimize medical outcomes. Orthopedic surgeons serving in the military may treat little to no trauma in their stateside practice. In conflict zones, however, the majority of their patients will have traumatic injuries. Determining risk factors for nonevidence-based practice can help identify provider knowledge gaps, which can then be targeted before deployment. Surveys were developed which sought to identify factors contributing to continued medical education and practice, as well as scenario-based questions on military-relevant orthopedic trauma. Analysis of 188 survey respondents revealed that providers with military service and less than 10 years of practice are optimally bridging research into military-relevant orthopedic trauma practice.